Integrating lncRNAs and mRNAs Expression Profiles in Penicillin-Induced Persistent Chlamydial Infection in HeLa Cells - Huang, Xiaobao; Liufu, Qian; Xu, Rui; Chen, Xiaohong; Liu, Mingna; Han, Jiande; Guan, Hongyu; Ma, Chunguang (Frontiers in Molecular Biosciences, 2022)
Chlamydia trachomatis (C. trachomatis) is a major etiological agent of sexually transmitted infection. Some stressing conditions can result in persistent chlamydial infection, which is thought to be associated with severe complications including ectopic pregnancy and tubal factor infertility. Long noncoding RNAs (lncRNAs) have been identified as key modulators in many biological processes. Nevertheless, the role of lncRNAs in persistent chlamydial infection is still unclear. In this study, we used lncRNA and mRNA microarray to identify the global lncRNAs and mRNAs expression in penicillin-induced persistent chlamydial infection in HeLa cells as well as the control group (HeLa cells without C. trachomatis infection). Among 1005 differentially expressed lncRNAs, 585 lncRNAs were upregulated and 420 downregulated in persistent chlamydial infection, while 410 mRNAs were identified to express differentially, of which 113 mRNAs were upregulated and 297 downregulated. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis with differentially expressed genes were performed. We then constructed the lncRNA-miRNA-mRNA competing endogenous RNAs (ceRNAs) network. Four mRNAs were validated to be changed by quantitative real-time PCR which were correlated with the microarray result. Integration of protein-protein interaction (PPI) network was constructed and hub genes were identified. These findings provide a new perspective on the molecular mechanism of penicillin-induced persistent chlamydial infection.